Architecture and planning students' awareness of ergonomic and work-related demands: A cross-sectional study in Riyadh, Saudi Arabia. - Shaheen, Afaf AM; Algabbani, Maha F (Work, 2026)
Background: Architecture students are at increased risk of musculoskeletal pain (MSP) due to extended sedentary work frequently performed in non-ergonomic postures. Objective: This study evaluates their awareness (current knowledge, practice, and attitude) of ergonomics and the prevalence of self-reported MSP. Methods: This descriptive cross-sectional study was applied to 123 students using a self-administered questionnaire. The questionnaire collected data on demographics, work nature, ergonomic awareness, work demands, and prophylactic remedies. Results: Most (73.2%) lacked prior knowledge of ergonomics, with a borderline association with female gender (P = 0.07). Twenty-five % of males and 28.5% of females were unaware of work-related risks associated with poor ergonomics. Female students reported poorer ergonomic practices than males, including lower adherence (47.1% vs. 30.1%, χ²=8.57, P = 0.01), inadequate workspaces (28% vs. 13%, χ²=7.56, P = 0.01), more frequent floor sitting (31.7% vs. 8.9%, χ²=14.39, P < 0.001), and fewer work breaks (χ²=14.39, P < 0.001). Despite this, 90.2% expressed positive attitudes toward ergonomics. The prevalence of self-reported musculoskeletal pain was high, especially among females, who reported more pain in the shoulders, upper back, wrists, and hands (p < 0.05). Conclusions: These findings underscore the need for targeted interventions, such as educational programs and ergonomic assessments, to raise awareness and prevent musculoskeletal pain among architecture students.